Migration of Blockchain Systems to Quantum Resistant Security ECDSA vs NIST MLDSA - Santika Lya Diah Pramesti; Yul Ifda Tanjung; Azwani Aulia; Muhammad Rafly Ramadhan; Ikyboy Van Versie (IAIC Bangun Bangsa, 2026)
The advent of cryptographically relevant quantum computers poses an existential threat to the security foundations of contemporary blockchain networks, which predominantly rely on the ECDSA for transaction authorization and identity management. Shor’s quantum algorithm can solve the underlying mathematical problems of ECDSA in polynomial time, rendering current ledgers vulnerable to catastrophic asset theft. This study aims to examine the implications of quantum computing on blockchain security by positioning ECDSA and ML-DSA as two generational digital signature standards within the evolving cryptographic landscape. The analysis is conducted through a standards-based comparative approach, focusing on the formal specifications and security objectives outlined in the U.S. NIST post-quantum cryptographic standard FIPS 204. The findings indicate that ECDSA and ML-DSA represent two critical generations of digital signature standards: ECDSA as the legacy cryptographic foundation for current blockchain ecosystems, and ML-DSA (formerly CRYSTALS-Dilithium) as the newly standardized, quantum-resistant successor mandated for future secure systems. This transition underscores the strategic importance of evaluating digital signature algorithms not only as cryptographic primitives but also as formal standards with far-reaching implications for public policy, regulatory compliance, and long-term protocol governance.